2021
DOI: 10.1073/pnas.2022933118
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a minimum amyloid fibril core formed by necroptosis-mediating RHIM of human RIPK3

Abstract: Receptor-interacting protein kinases 3 (RIPK3), a central node in necroptosis, polymerizes in response to the upstream signals and then activates its downstream mediator to induce cell death. The active polymeric form of RIPK3 has been indicated as the form of amyloid fibrils assembled via its RIP homotypic interaction motif (RHIM). In this study, we combine cryogenic electron microscopy and solid-state NMR to determine the amyloid fibril structure of RIPK3 RHIM-containing C-terminal domain (CTD). The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…This is likely due to the fact that helical symmetry only indicates the upper limit on the helical twist for a fibril of a given radius and does not impose a lower bound on helical twist for a fibril of a given radius. Figure 5 is also consistent with the correlation found by Wu, et al between the number of residues in the fibril core (a proxy for fibril width) versus fibril pitch when they correctly identified that the very small core of RIPK3 fibrils in their study allowed for a large helical twist (the bottom- and left-most point on Figure 5) 11 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This is likely due to the fact that helical symmetry only indicates the upper limit on the helical twist for a fibril of a given radius and does not impose a lower bound on helical twist for a fibril of a given radius. Figure 5 is also consistent with the correlation found by Wu, et al between the number of residues in the fibril core (a proxy for fibril width) versus fibril pitch when they correctly identified that the very small core of RIPK3 fibrils in their study allowed for a large helical twist (the bottom- and left-most point on Figure 5) 11 .…”
Section: Resultssupporting
confidence: 89%
“…For the analysis of the pitch and radius of the Pick’s Disease Wide Fibril used in Figure 5, we downloaded the Wide Fibril map and Narrow Fibril model from the PDB and built a hypothetical Wide Fibril model as the authors propose in Falcon, et al by rigid-body fitting two Narrow Fibrils into the Wide Fibril map 23 . We measured the maximum radius of the theoretical Wide Fibril and calculated its pitch using the Wide Fibril helical parameters from Falcon, et al For the RipK3 fibril 11 , we included radius and twist parameters in Fig. 5, but did not calculate hydrogen bonding parameters due to the low resolution of the cryo-EM map and the resulting uncertainty in the atomic model.…”
Section: Methodsmentioning
confidence: 99%
“…However, while chiral monomers may display a preference for a given helical hand in the corresponding assemblies, this correlation is not necessarily absolute (Harper et al ., 1997; Chamberlain et al ., 2000). Twist polymorphism, in which a chiral peptide monomer can assemble into either a right-handed or left-handed supramolecular enantiomorph, has been observed for amyloid fibrils assembled in vivo or in vitro (Usov et al ., 2013; Kollmer et al ., 2019; Wu et al ., 2021). This phenomenon may also apply to helical filaments derived from self-assembly of designed peptides and peptido-mimetic foldamers.…”
Section: Structures Of Helical Peptide Assembliesmentioning
confidence: 99%
“…Preliminary SSNMR analysis of the recombinant PP motif revealed the formation of well-ordered amyloid fibrils rich in β-sheet structure ( Daskalov et al, 2016 ). A structural model of RIP1-RIP3 has been proposed based on SSNMR structural information ( Mompeán et al, 2018 ), recently complemented by the structure of RIPK3 solved by cryo-EM in combination with SSNMR ( Wu et al, 2021 ), and it remains to be solved if the sequence similarity between fungal and mammals necroptotic amyloid motifs translate into structure similarity.…”
Section: Functional Prions Emerge As Trans -Kingdom Entitiesmentioning
confidence: 99%